Design of inductive electrostatic boom spray system based on embedded closed electrode structure and droplet distribution test in soybean field - Liu, Changxi; Hu, Jun; Cao, Rui; Li, Yufei; Zhao, Shengxue; Li, Qingda; Zhang, Wei (Frontiers in Plant Science, 2024)
The large water demand, insufficient deposition on the back of the leaf and the uneven distribution of droplets are the problems of traditional agricultural ground plant protection machinery, which leads to low agricultural control efficiency. Combined with the advantages of electrostatic spray technology and the characteristics of high working efficiency and low probability of droplets drift of ground sprayer, an inductive electrostatic boom spray system based on embedded electrode structure is designed and mounted on a large self-propelled boom sprayer for field testing. Based on the working characteristics of the fan nozzle and the analysis of the theory of charge, the inductive electrostatic spray device is designed. The performance of the device is tested and the rationality of the system design is verified by COMSOL numerical simulations, charge-to-mass ratio, and particle size distribution measurements. The spray deposition scanning software and the Box-Behnken experimental design method are used to analyze the spray droplet deposition rate and coverage density of the sprayer on the front and back of the target leaves. The results show that the embedded closed electrode structure designed in this paper can avoid the problem of electrode wetting, and the electric field generated by it is mainly concentrated in the spray liquid film area, and the intensity reaches 6⁓7 V/m. At the conventional application height (500 mm), the maximum charge-to-mass ratio is 2.91 mC/kg, and the average particle size is 168.22 μm, which is 12.87% lower than that of ordinary spray, when the spray pressure is 0.3 MPa and the electrostatic voltage is 12 kV. The results of field experiments show that the optimum combination of the working parameters with the spray speed is 8.40 m/s, the spray pressure is 0.35 MPa, the charging voltage is 11.50 kV, the amount of droplet deposition in the lower dorsal area of the blade is 1.44 µL•cm -2 .